2023
DOI: 10.1080/19490976.2023.2221778
|View full text |Cite
|
Sign up to set email alerts
|

L-Arabinose inhibits Shiga toxin type 2-converting bacteriophage induction in Escherichia coli O157:H7

Abstract: The pathogenicity of Escherichia coli (E. coli) O157:H7 is predominantly associated with Shiga toxin 2 (Stx2) that poses a huge threat to human and animal intestinal health. Production of Stx2 requires expression of stx2 gene, which is located in the genome of lambdoid Stx2 prophage. Growing evidence has implicated that many commonly consumed foods participate in the regulation of prophage induction. In this study, we aimed to explore whether specific dietary funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…L-Arabinose can improve intestinal health by manipulating the composition of the gut microbiota 61 . A recent study found that L-arabinose inhibits Shiga toxin type 2-converting bacteriophage induction in EHEC O157:H7 62 . Lithocholic acid and deoxycholic acid are secondary bile acids that are prevalent in the cecum and colon of mice and humans 63,64 .…”
Section: Mkmentioning
confidence: 99%
“…L-Arabinose can improve intestinal health by manipulating the composition of the gut microbiota 61 . A recent study found that L-arabinose inhibits Shiga toxin type 2-converting bacteriophage induction in EHEC O157:H7 62 . Lithocholic acid and deoxycholic acid are secondary bile acids that are prevalent in the cecum and colon of mice and humans 63,64 .…”
Section: Mkmentioning
confidence: 99%